Molecular cloning and sequencing of cDNA for yeast porin, an outer mitochondrial membrane protein: a search for targeting signal in the primary structure. - Mihara, K (1985)
We have cloned a full-length cDNA for yeast porin, the major outer mitochondrial membrane protein from Saccharomyces cerevisiae, and determined its nucleotide sequence. The primary structure of the protein, deduced from the nucleotide sequence, consisted of 283 amino acid residues and its NH2-terminal sequence, Met-Ser-Pro-Pro-Val-Tyr-Ser, coincided with that determined by Edman degradation for yeast porin, except that the initiator methionine was missing in the mature protein. The deduced sequence had an overall polarity index of 46.3%, a value which falls in the normal range for soluble proteins. An evaluation of hydropathy of the protein indicated that the NH2-terminal one third was relatively hydrophilic and the rest of the molecule was rather hydrophobic. An interesting finding was that the NH2-terminal region of yeast porin (consisting of some 50 amino acid residues) shows structural features that resemble those of the corresponding portion of 70-kd protein, which is also a yeast outer mitochondrial membrane protein. We postulate that this NH2-terminal sequence, like that of 70-kd protein, is required for targeting the porin to the outer mitochondrial membrane.